Kinetics coefficient of palm oil clinker media for an attached growth media in sequencing batch reactor mode - Kuan, Y.Z. (Polish Society of Ecological Engineering (PTIE), 2019)
Palm oil clinker media (POCM), which is a by-product of incineration process from palm oil industry, creates environmental sustainability issues. This is due to the method of handling solid waste material of industry by simply dumping it on an open land area. The previous study of POCM including physical and mechanical properties of solid present showed promising results of utilizing POCM as a packing media for treatment of domestic wastewater industry. The packing media can be used in the process of biological wastewater treatment system in Sequencing Batch Reactor (SBR) mode. By adopting POCM as an attached growth media, this research paper focuses on the performance of POCM in SBR mode in the context of organic and nutrient removal rate. The performance pertaining to the removal of organics and nutrient was measured using USEPA Standard Method for Chemical Oxygen Demand (COD) and Ammonia. The average rate of removal for COD and Ammonia per biomass adopting POCM in sequencing batch reactor mode is 0.0069 mg COD/mg MLVSS and 0.001 mg Ammonia/mg MLVSS. Â© 2019, Polish Society of Ecological Engineering (PTIE).